2017
DOI: 10.1038/s41598-017-00592-z
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-Related Changes in Species Spatial Niche Overlaps in Spring Communities

Abstract: Species interactions between stygobites (obligate groundwater organisms) are poorly known, reflecting the difficulty in studying such organisms in their natural environments. Some insight can be gained from the study of the spatial variability in microcrustacean communities in groundwater-fed springs. Earthquakes can increase hydraulic conductivity in the recharge area of karstic aquifers and flow rates in discharge zones, thus dislodging stygobites from their original habitats to the spring outlets. Earthquak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…In this study, the variance explained by the univariate models was low and this indicated that further factors, in addition to those already investigated, must be taken into account in the future to better explain the observed biological patterns. For instance, copepod species interactions could play a role in determining the biological assemblages in VO_GWB as already observed in other aquifers [74]. Similarly, previous studies showed that the grain size composition of sediments [75][76][77], and the lowering of the groundwater table [21,75], could influence the biological assemblage's patterns in alluvial aquifers.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, the variance explained by the univariate models was low and this indicated that further factors, in addition to those already investigated, must be taken into account in the future to better explain the observed biological patterns. For instance, copepod species interactions could play a role in determining the biological assemblages in VO_GWB as already observed in other aquifers [74]. Similarly, previous studies showed that the grain size composition of sediments [75][76][77], and the lowering of the groundwater table [21,75], could influence the biological assemblage's patterns in alluvial aquifers.…”
Section: Discussionsupporting
confidence: 57%
“…A number of overlap metrics have been developed for ecological applications. These metrics have been applied to diverse ecological questions, including the examination of niche equivalency of species in environmental space (Broennimann et al, 2012;Warren, Glor, & Turelli, 2008), overlap of animal home ranges (Fieberg & Kochanny, 2005), overlap in dietary niche among competitors (Woodward & Hildrew, 2002), and changes in resource partitioning among species after environmental perturbations (Fattorini et al, 2017). Several reviews of overlap metrics have discussed their mathematical and biological properties and have investigated sources of bias and error (e.g., Hurlbert, 1978;Krebs, 1989;Rödder & Engler, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017). For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017).…”
Section: Environmental Stochasticitymentioning
confidence: 99%
“…Taking advantage of local site-specific phenomena, such as earthquakes, floods and volcanic eruptions, a few authors have recently shown that subterranean habitats may actually represent unusual, yet promising systems in which to investigate environmental stochasticity. For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017). Ortuño et al (2013) showed how periodic flooding may extirpate native community in specific subterranean habitats (the so-called 'Alluvial MSS'), enhancing the possibility to use these systems to study re-colonization processes and meta-population dynamics, just like in the famous case of the Krakatau Islands (Thornton et al 1988, Whittaker et al 1989.…”
Section: Environmental Stochasticitymentioning
confidence: 99%